2022
DOI: 10.3389/fpsyg.2022.851120
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Academic Procrastination on Second Language Writing: The Mediating Role of L2 Writing Anxiety

Abstract: Recently, there has been a surge of interest in the exploration of psychological properties in a second language context. Considerable literature has grown up around the influence of these psychological properties on L2 writing specifically. However, the impact of academic procrastination, which is an important psychological property, has been understudied and it remains unclear how affective factors in L2 might play a role in the above potential influence on L2 writing. Therefore, the current study explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 60 publications
(63 reference statements)
4
14
0
Order By: Relevance
“…The findings regarding Chinese EFL learners' experience of Cognitive Anxiety in the present study are also in line with those of previous research in some aspects. As has been mentioned, according to some of the previous studies, EFL learners in China usually experienced Cognitive Anxiety the most (Chiang, 2012;Sun and Fan, 2022;Zhang and Zhang, 2022), while those outside China did not.…”
Section: Cognitive Anxiety In L2 Writing Processmentioning
confidence: 86%
See 2 more Smart Citations
“…The findings regarding Chinese EFL learners' experience of Cognitive Anxiety in the present study are also in line with those of previous research in some aspects. As has been mentioned, according to some of the previous studies, EFL learners in China usually experienced Cognitive Anxiety the most (Chiang, 2012;Sun and Fan, 2022;Zhang and Zhang, 2022), while those outside China did not.…”
Section: Cognitive Anxiety In L2 Writing Processmentioning
confidence: 86%
“…All in all, these studies of SLWA indicated that EFL learners in China usually experienced Cognitive Anxiety the most (Chiang, 2012;Sun and Fan, 2022;Zhang and Zhang, 2022), while EFL learners outside China usually experienced Avoidance Behavior the most (Xiao and Wong, 2014;Salem, 2022). No research on SLWA has attended to these differences, as their research focus was usually on the multi-dimensional nature of anxiety, or other variables related to anxiety.…”
Section: Second Language Writing Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…3 Studies have shown that academic procrastination not only affects students' academic performance [4][5][6] but also may cause them negative emotions, 7 such as anxiety about exams and academic tasks. 8,9 In addition, some researchers have found that there is also a significant relationship between academic procrastination and externalizing problems in forms such as problematic internet usage. 10 Previous studies on academic procrastination have mostly focused on college students, and few studies have researched middle school students, specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Scholarly attention has thus been steered to a much broader exploration of domain-general psychological properties in the L2 context more recently. Grit ( Liu and Wang, 2021 ), resilience ( Li, 2022 ), academic procrastination ( Zhang and Zhang, 2022 ) and enjoyment ( Dewaele and Alfawzan, 2018 ) etc. were at the centre of the discussion.…”
Section: Introductionmentioning
confidence: 99%